Answer:
C. (9, 26)
Explanation:
By Substitution:
y = 2x + 8
y = 3x - 1
---------------------
2x + 8 = 3x - 1
-x + 8 = -1
-x = -9
x = 9
Now we can choose either of the two equations given to solve for y:
y = 2x + 8
y = 2(9) + 8
y = 18 + 8
y = 26
(9, 26)
By Elimination:
For this process, I am going to rewrite the equation in "x + y" for as it will make it easier to eliminate the variables
y = 2x + 8
2x - y = -8
y = 3x - 1
-3x + y = -1
-----------------
2x - y = -8
-3x + y = -1
-----------------
-x = -9
x = 9
2x - y = -8
2(9) - y = -8
18 - y = -8
-y = -26
y = 26
(9, 26)